(3GdebGeGJs - (3CHh eMeO GdbGSe Hf Ydj Hf eMeO Hf YKeGf GdMQjQj GdHUQj, GdMQjQj,J (B516 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3Gddge EfG fMeOc Ydi eG YdeJ ef GdHjGf hCdgeJ ef GdJHjGf s
(3BNQgG (B:s
(3JeJ GdebGeGJ HMeO Gddg hefg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B12s
Keywords: (3GdCOHs